Assessment nurses' knowledge level about procedure of blood transfusion - Hana'a Hussein Mukhlif; Noor Saad Khalil (College of Nursing,University of Mosul, 2017)
Background: Nurses' role is warned to view blood transfusion responsibilities, and able to identify the nursing required to care for patients receiving a blood transfusion so that they can develop their skills. The aimed of the study to assess nurses' knowledge level procedure of blood transfusion. Materials and method: A descriptive study approach was carried out at Al-Salam teaching hospital in Mosul city. A random sample consists of (130) nurses, the questionnaire was used for data collection, it include two parts. Part one was demographic data, and Part two including (16) questions for nurses' knowledge of blood transfusion. Content validity was determined by presenting the items to a panel of (10) experts, and used the Coefficient Correlation for questionnaire items showed that the reliability of the questionnaire which was (r = 0.90). Results: The study finding that there average of true answers (64%), while (36%) false answers of nurses' knowledge of blood transfusion procedure for the patient. Also the present study indicates (65%) of nurses have good knowledge and (35%) of nurses has poor knowledge about procedure of blood transfusion. Conclusions: The present study showed that a third of nurses' have poor knowledge of blood transfusion, and finding a significant relationship between the nurses knowledge and level of education, also a significant relationship between the nurses' knowledge and course trainings. Keywords: Assessment, Nurses Knowledge, Blood Transfusion.